Identifying optimal PD-1/PD-L1 inhibitors in first-line treatment of patients with advanced squamous non-small cell lung cancer in China: Updated systematic review and network meta-analysis - Zhao, Mingye; Shao, Taihang; Ren, Yinan; Zhou, Caicun; Tang, Wenxi (Frontiers in Pharmacology, 2022)
Objective After Gemstone-302 was published in Lancet in January 2022, seven PD-(L)1 inhibitors launched or about to be launched in China, but there are no head-to-head RCTs reporting the comparative efficacy for squamous non-small cell lung cancer (sq-NSCLC). Therefore, this study aims to indirectly compare the efficacy of these treatments to provide evidence for clinical decision and Chinese national reimbursement drug listing. Methods We collected phase III clinical trials targeted on stage IIIB–IV patients for first-line immunotherapy of sq-NSCLC by systematically searching databases and conference abstracts. Chemotherapy was limited to paclitaxel/gemcitabine plus platinum. Relative effects of competing treatments were assessed by Bayesian network meta-analysis. Hazard ratios (HR), serious adverse events (SAEs), progression-free survival years (PFS) and overall survival years (OS) were the outcomes. We performed sensitivity analysis using the range of parameters distribution as well as different comparison methods to test the robustness of the results. Results 7 clinical trials with 2640 patients were included. For OS, the efficiency ranks from high to low were sugemalimab (HR, 0.48; 95%CI, 0.32-0.73), camrelizumab (HR, 0.55; 95%CI, 0.40-0.76), sintilimab (HR, 0.56; 95%CI, 0.35-0.90), pembrolizumab (HR, 0.71; 95%CI, 0.58-0.87) and atezolizumab (HR, 0.88; 95%CI, 0.73-1.05). For PFS, the efficiency ranks from high to low were sugemalimab (HR, 0.33; 95%CI, 0.24-0.45), camrelizumab (HR, 0.37; 95%CI, 0.30-0.46), tislelizumab (HR, 0.53; 95%CI, 0.36-0.79), sintilimab (HR, 0.54; 95%CI, 0.42-0.69), toripalimab (HR, 0.56; 95%CI, 0.38-0.83), pembrolizumab (HR, 0.57; 95%CI,0.47-0.70) and atezolizumab (HR, 0.71; 95%CI, 0.59-0.85). Proportional hazard models and non-proportional hazard models showed consistent efficiency ranks. When extrapolated to long-term survival benefit, under non-proportional hazard ratio, sugemalimab achieved the highest PFS benefit in 2 years (1.323 LYs), with camrelizumab (1.320 LYs), sintilimab (1.243 LYs), tislelizumab (1.189 LYs), pembrolizumab (0.990 LYs) and atezolizumab (0.947 LYs) ranking in order; Camrelizumab achieved the highest OS benefit in 10 years (2.723 LYs), with atezolizumab (2.445 LYs) and pembrolizumab (2.397 LYs) ranking in order. In terms of safety, PD-(L)1 drugs increased the incidence of SAEs when combined with chemotherapy, camrelizumb and sugemalimab were the safest drugs. Conclusions Sugemalimab is superior both in HR and long-term survival benefit for Chinese patients with advanced sq-NSCLC.